Pengaruh Leverage dan Firm Size Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur di BEI Subsektor Heavy Contructions dan Civil Engineering (2022-2023) - Perwindasari, Novita Ika; Jefri, Riny (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to examine the effect of leverage and firm size on the financial performance of companies in the heavy construction and civil engineering subsector listed on the Indonesia Stock Exchange during 2022 to 2023. The research employs a quantitative approach with a causal design. The sample was selected using purposive sampling based on the criteria of companies consistently publishing complete financial statements during the two-year observation period, resulting in 21 companies with 42 observations. Data were analyzed using multiple linear regression preceded by classical assumption tests to ensure model validity. The findings indicate that leverage, measured using the Debt to Asset Ratio, has a significant negative effect on Return on Assets, while firm size shows no significant effect. Simultaneously, both independent variables influence profitability, although their explanatory power remains limited. These findings highlight the importance of managing capital structure within construction companies and demonstrate that asset size alone does not guarantee higher profitability without effective operational efficiency.